Effect of combined laser dyes on the efficiency of cholesteric liquid crystal lasers - Hamidreza Shirvani-Mahdavi; Soheila Ebrahimi-Azandariani (Journal of Theoretical and Applied Physics)
Abstract A high efficiency band-edge cholesteric liquid crystal (CLC) laser comprising an optimal binary-dye mixture (OBD) with 62 wt% DCM and 38 wt% PM597 as the active medium is scrutinized. The measurements indicate that both the fluorescence spectrum width and the order parameter of OBD in the host of nematic liquid crystal (BL009) enhance compared with those for each individual dye. Furthermore, at the fluorescence peak, the optical efficiency of the PM597-doped CLC laser is ~ 1.5× higher than that of DCM, and the laser emission energy for OBD-doped CLC between the wavelengths 595 nm and 613 nm is even higher than that of PM597-doped CLC, so that at the maximum fluorescence of OBD, $$λ ≈ 605\;{\text{nm}}$$ λ≈605nm , the improvement is over 20%.